2017
DOI: 10.15388/informatica.2017.142
|View full text |Cite
|
Sign up to set email alerts
|

Improved Asymmetric Cipher Based on Matrix Power Function Resistant to Linear Algebra Attack

Abstract: In this paper we consider an improved version of earlier published asymmetric encryption protocol based on matrix power function (MPF). Recently, a linear algebra attack on earlier version of this protocol was found. This attack allows an attacker to break suggested protocol in polynomial time. Here we show that the improved version of our encryption protocol is not vulnerable to the declared linear attack, while retaining its effective realization in embedded systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The authors of the latter paper showed that the system of matrix equations used to find the private key of Alice (or Bob) can be transformed to a system of linear equations and hence mentioned protocols can be broken in polynomial time. Eventually, we were able to evade this attack in our paper [21]. We also performed an investigation of public parameter generation issues in [22].…”
Section: Our Previous Contributions and Novelty Of This Papermentioning
confidence: 97%
See 1 more Smart Citation
“…The authors of the latter paper showed that the system of matrix equations used to find the private key of Alice (or Bob) can be transformed to a system of linear equations and hence mentioned protocols can be broken in polynomial time. Eventually, we were able to evade this attack in our paper [21]. We also performed an investigation of public parameter generation issues in [22].…”
Section: Our Previous Contributions and Novelty Of This Papermentioning
confidence: 97%
“…where L ∈ Mat(Z τ ) is some fixed publicly known matrix. Example with more complicated linear span of matrices was presented in [21]. We also analyzed this linear span in greater detail in [22].…”
Section: Description Of Mpf and Its Basic Propertiesmentioning
confidence: 99%
“…The authors of [16] also suggested some improvements of our protocols to resist the proposed attack. In [7] we fixed this flaw for the asymmetric encryption protocol, presented in [1]. The intriguing idea was to extend MPF construction to non-commutative algebraic structures, namely S and R, hence expecting higher complexity of MPF problem and achieving a higher potential security for the construction of cryptographic primitives.…”
Section: Remarkmentioning
confidence: 99%
“…Some cryptographic primitives were built on the basis that MPF is a conjectured OWF in [1][2][3][4][5]. Furthermore, some results were published considering the security of presented primitives in [6][7][8]. The security of these primitives is based on the complexity of MPF inversion named as MPF problem.…”
Section: Introductionmentioning
confidence: 99%
“…Some novel solutions are even improvements of concepts well known to the automobile industry (i.e. car keys) (Grosse and Upadhyay, 2013); others are based asymmetric cyphers (Sakalauskas and Mihalkovich, 2017), on certificateless key encapsulations (Gao et al, 2017;Wu et al, 2018), ID-based cryptography (Meshram et al, 2017), or image-based encryption (Khan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%